2021
DOI: 10.3389/fneur.2021.768456
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Loss of Bdnf Affects Peripheral but Not Central Vestibular Targets

Abstract: The vestibular system is vital for proper balance perception, and its dysfunction contributes significantly to fall-related injuries, especially in the elderly. Vestibular ganglion neurons innervate vestibular hair cells at the periphery and vestibular nuclei and the uvula and nodule of the cerebellum centrally. During aging, these vestibular ganglion neurons degenerate, impairing vestibular function. A complete understanding of the molecular mechanisms involved in neurosensory cell survival in the vestibular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Recent evidence indicates that primary inputs from the vestibular organs (include afferents innervating the Emx2-positive region) and secondary inputs from the vestibular nuclei (include receiving inputs from afferents innervating the Emx2-negative region) both converge on different subtypes of unipolar brush cells in the cerebellum 35 . Since unipolar brush cells normally converge to the granule cells 36 , this could be one of the locations where inputs from Emx2-positive and negative regions are combined and integrated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence indicates that primary inputs from the vestibular organs (include afferents innervating the Emx2-positive region) and secondary inputs from the vestibular nuclei (include receiving inputs from afferents innervating the Emx2-negative region) both converge on different subtypes of unipolar brush cells in the cerebellum 35 . Since unipolar brush cells normally converge to the granule cells 36 , this could be one of the locations where inputs from Emx2-positive and negative regions are combined and integrated.…”
Section: Discussionmentioning
confidence: 99%
“…The vestibular HC loss in mice might be due to the gradually lost connections with vestibular ganglion neurons over the first 6 months of life. 55 Previous studies have tended to attribute the loss of SC plasticity to cytoskeletal changes. Cross‐species SC comparisons have shown that SC regenerative ability is associated with intercellular junctions, 56 , 57 and there is no denying that cytoskeletal changes affect the cell's ability to alter its morphology, which hinders postnatal SC proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…(2021) investigated the effects of the loss of Bdnf , which leads to the significant loss of HCs at the periphery in very old mice after loss of vestibular neurons. The vestibular HC loss in mice might be due to the gradually lost connections with vestibular ganglion neurons over the first 6 months of life 55 . Previous studies have tended to attribute the loss of SC plasticity to cytoskeletal changes.…”
Section: Discussionmentioning
confidence: 99%
“…Stacks of images were converted into CorelDraw to generate the images. In addition, we used two unpublished images from previous works that document the organization of cristae in mice (Elliott et al, 2021).…”
Section: Methodsmentioning
confidence: 99%